Dialogues in Urban Planning : Towards Sustainable Regions. - Gilmour, Tony.; Blakely, Edward J.; Pizarro, Rafael E. (Sydney : Sydney University Press, 2008)
In an age when the buzzword is 'sustainability', why do we continue to build unsustainable cities and regions? This book brings planners back to the centre of the debate. It shows that sustainability can no longer just apply to the subfield of planning called 'environmental planning' but has to permeate all aspects: housing, economic development, transport, regional coordination and urban design.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books